Strategi Bidang Instruktor dan Tenaga Pelatihan (INTALA) dalam Meningkatkan Kompetensi Profesional Instruktor TIK di BBPVP Serang - Averoes, Pinky Mesara; Purwaningsih, Nining (Lembaga Yasin AlSys, 2025)
This study is motivated by the importance of having competent and professional ICT instructors as a key factor in producing graduates from training programs capable of competing in the digital era. The objective of this research is to analyze the strategies implemented by the Instructor and Training Personnel (INTALA) in enhancing the professional competencies of Information and Communication Technology (ICT) instructors at the Vocational and Productivity Development Center (Balai Besar Pengembangan Vokasi dan Produktivitas) in Serang. The approach used is descriptive qualitative with data collection techniques through in-depth interviews, observation, and documentation studies. The results indicate that (1) the competencies of ICT instructors at BBPVP Serang have met professional standards, characterized by effective mastery of subject matter and teaching methodology; (2) the strategies implemented by INTALA include the Methodology Training Program, Technical Upgrading Training, and Soft Skills Strengthening Training; (3) supporting factors in the implementation of INTALA strategies include the availability of adequate training resources, encompassing facilities, infrastructure, and relevant teaching materials. However, there are several inhibiting factors affecting the effectiveness of implementation, namely the low motivation of some instructors, limited time to participate in competency development activities, and personal constraints that affect optimal participation.